Characterization of the accessory protein ClpT1 from Arabidopsis thaliana: oligomerization status and interaction with Hsp100 chaperones - Colombo, Clara Victoria (2014)
El presente articulo se encuentra aceptado con modificaciones. Background: The caseinolytic protease (Clp) is crucial for chloroplast biogenesis and proteostasis. The Arabidopsis Clp consists of two heptameric rings (P and R rings) assembled from nine distinct subunits. Hsp100 chaperones (ClpC1/2 and ClpD) are believed to dock to the axial pores of Clp and then transfer unfolded polypeptides destined to degradation. The adaptor proteins ClpT1 and 2 attach to the protease, apparently blocking the chaperone binding sites. This competition was suggested to regulate Clp activity. Also, monomerization of ClpT1 from dimers in the stroma triggers P and R ring association. So, oligomerization status of ClpT1 seems to control the assembly of the Clp protease. Results: In this work, ClpT1 was obtained in a recombinant form and purified. In solution, it mostly consists of monomers while dimers represent a small fraction of the population. Enrichment of the dimer fraction could only be achieved by stabilization with a crosslinker reagent. We demonstrate that ClpT1 specifically interacts with the Hsp100 chaperones ClpC2 and ClpD. In addition, ClpT1 stimulates the ATPase activity of ClpD by more than 50% when both are present in a 1:1 ratio. Outside this optimal proportion, the stimulatory effect of ClpT1 on the ATPase activity of ClpD declines. Conclusions: The accessory protein ClpT1 behaves as a monomer in solution. It interacts with the chloroplastic Hsp100 chaperones ClpC2 and ClpD and tightly modulates the ATPase activity of the latter. Our results provide new experimental evidence that may contribute to revise and expand the existing models that were proposed to explain the roles of this poorly understood regulatory protein.